A nomogram to predict the risk of relapse in patients with minimal change disease: a retrospective cohort study - Lefeng Wang; Qinfan Yao; Ying Zhang; Xuan Zhang; Mengjie Hu; Jianpeng Chen; Xiayu Li; Jianghua Chen; Heng Li (Renal Failure)
Background Minimal change disease (MCD) is a common pathological type of nephrotic syndrome. Relapses of MCD present a significant challenge for patients. This study aims to develop a predictive model for evaluating the probability of relapse in patients with MCD.Methods This study enrolled 152 patients with biopsy-confirmed MCD, all of whom received exclusive glucocorticoid treatment at the First Affiliated Hospital of Zhejiang University in Hangzhou, China, between October 2012 and April 2021. The Cox regression analysis was utilized to identify the risk factors associated with the relapse in MCD, and a nomogram was constructed to predict the probability of relapse.Results The results demonstrated that serum immunoglobulin E (IgE) levels > 936 IU/mL, age ≤ 30 years old, estimated glomerular filtration rate (eGFR) < 90 mL/(min × 1.73 m2), serum total cholesterol (TCh) levels > 12.3 mmol/L, and time to remission were independent risk factors associated with relapses in patients with MCD. A nomogram was established and achieved a concordance index of 0.726 (95% CI = 0.659–0.793). The receiver operating characteristic curves demonstrated areas under the curve of 0.771, 0.853, and 0.811 for the prediction of relapse at 1-, 2-, and 3-year intervals after achieving remission in MCD patients respectively. These findings along with the calibration curves indicated the good discrimination and calibration performance of the nomogram in this cohort.Conclusion: The established nomogram provides a valuable tool for the identification of patients with MCD who are at risk of relapse, which may facilitate prompt treatment for these patients.